Lachnospiraceae are emerging industrial biocatalysts and biotherapeutics - Zaplana, Tom; Miele, Solange; Tolonen, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2024)
The Lachnospiraceae is a family of anaerobic bacteria in the class Clostridia with potential to advance the bio-economy and intestinal therapeutics. Some species of Lachnospiraceae metabolize abundant, low-cost feedstocks such as lignocellulose and carbon dioxide into value-added chemicals. Others are among the dominant species of the human colon and animal rumen, where they promote healthy gut and immune function. Here, we summarize recent studies of the physiology, cultivation, and genetics of Lachnospiraceae, highlighting their wide substrate utilization and metabolic products with industrial applications. We examine studies of these bacteria as Live Biotherapeutic Products (LBPs), focusing on in vivo disease models and clinical studies using them to treat infection, inflammation, metabolic syndrome, and cancer. We discuss key research areas including elucidation of intra-specific diversity and genetic modification of candidate strains that will facilitate the exploitation of Lachnospiraceae in industry and medicine.